The effect of sapstain fungi on wood quality / Muhammad Firdaus Dan - Dan, Muhammad Firdaus (2007)
The wood value is valid by its physical properties for the most. It means that its surface appearance is very important where it has high aesthetical value. If something happen to the surface of the wood, it can reduce the wood quality. The sapstain fungal is the main cause of wood discoloration which reduces the wood quality. The sapstain is innocuous but it can't be removed by planning or trimming when it already affects the wood. When this problem occurs, the timber or log quality will be reflects as well. The timber trade value for those woods will decrease. The medium for transporting these fungi is wind and air. When there was too much of sapstain fungi in wood, the wood decay resistance will decrease and as a result, decaying fungi will appear and reduce the wood strength. To avoid this problem, the wood must be treated by preserving or storing kiln drying it until the wood's moisture content reach the safe level from fungal attack. Besides, the chemical that has been used must be carefully handled so it won't pollute the environment.